Martin's big words - Rappaport, Doreen; Duncan, Michael Clarke (Danbury : Weston Woods Studios, a subsidiary of SCHOLASTIC Inc, 2007)
Looks at the life of Dr. Martin Luther King, explaining his work to bring about a peaceful end to segregation.
Unabridged.
Narrator: Michael Clarke Duncan.
3-6.
AD610L
3.4
Requires OverDrive Listen (file size: N/A KB) or OverDrive app (file size: 4637 KB).
Keywords: Juvenile Nonfiction; Electronic books; King, Martin Luther, -- Jr., -- 1929-1968 -- Juvenile literature; King, Martin Luther, -- Jr., -- 1929-1968 -- Quotations -- Juvenile literature; African Americans -- Biography -- Juvenile literature; Civil rights workers -- United States -- Biography -- Juvenile literature; Baptists -- United States -- Clergy -- Biography -- Juvenile literature; African Americans -- Civil rights -- History -- 20th century -- Juvenile literature; Civil rights workers; Clergy; Civil rights workers -- Biography; Clergy -- Biography; Caldecott honor book; SORA Audiobook